Comparative Study of Imprint Cytology and Frozen Section in the Intraoperative Diagnosis of Thyroid Lesions (Bangladesh Journal of Pathology, 2009)
Imprint cytology can provide a useful adjunct to the frozen section diagnosis and may be used safely in the intraoperative diagnosis of thyroid nodules, especially in the centres where frozen section facilities are not available. This study was conducted to compare imprint cytology and frozen section in terms of diagnostic accuracy, sensitivity, specificity, positive predictive value and to assess the value of imprint cytology in the intraoperative diagnosis of thyroid lesions. A total of 57 consecutive patients were enrolled in the study. All of the patients underwent frozen section in the department of pathology, BSMMU, Dhaka. Imprints were taken from the fresh specimen sent for frozen section from departments of otolaryngology and surgery of BSMMU. Imprint slides were stained with rapid H & E staining method. Then the tissues were submitted for frozen section by standard method. In this study, diagnostic accuracy, sensitivity, specificity, positive predictive value and negative predictive value of imprint cytology were 81.25%, 66.66%, 82.59%, 87.12% respectively. Frozen section revealed the diagnostic accuracy, sensitivity, specificity, positive predictive value and negative predictive as 88.46%, 72.72%, 100%, 100%, 83.33% respectively. Imprint cytology was found to be comparable with frozen section in diagnostic accuracy and sensitivity. Since imprint cytology is a simple and cost-effective procedure it can be used as an alternative to frozen section in hospitals where frozen section facilities are not available. Key Words: Imprint cytology, frozen section, intraoperative diagnosis of thyroid lesions  doi: 10.3329/bjpath.v24i1.2876 Bangladesh J Pathol 24 (1) : 12-15